MicroRNA-342 Promotes the Malignant-Like Phenotype of Endometrial Stromal Cells via Regulation of Annexin A2. (17th May 2021) - Sun, Dan; Wang, Yiting; Wang, Li; Guo, Xin
Abstract : The relevance of miRNA- (miR-) 342 to endometriosis has been highlighted, while its function in regulating the malignant-like phenotype of endometrial stromal cells which demonstrate epigenetic abnormalities that alter expression of transcription factors, remains unclear. Therefore, we sought to characterize the effects of miR-342 in endometrial stromal cell proliferation by regulating Annexin A2 (ANXA2). We first characterized the levels of miR-342 and ANXA2 in 31 cases of normal endometrium from patients with grade II-III cervical intraepithelial neoplasia or patients with hysterectomy versus ectopic endometrial tissues of 42 patients with endometriosis. miR-342 was upregulated, while ANXA2 was downregulated in ectopic endometrial tissues. Bioinformatics website and dual-luciferase reporter assay revealed that miR-342 negatively modulated ANXA2 expression. Following loss- and gain-of-function approaches, CCK-8, Transwell, and flow cytometry demonstrated that overexpression of miR-342 markedly increased cell proliferation, migration, and invasion but inhibited cell apoptotic ratio of endometrial stromal cells, which was reversed by ANXA2 elevation. Further, overexpressed miR-342 activated the PI3K/AKT/mTOR signaling pathway, as evidenced by upregulated levels of p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR. Taken together, miR-342 targets ANXA2 to activate the PI3K/AKT/mTOR signaling pathway, thereby promoting the malignant-like phenotype of endometrial stromal cells, highlighting miR-342 inhibition as a promising approach for the treatment of endometriosis.